Stability of Volterra system with impulsive effect. (1991) - Rao, M. Ramamohana; Sivasundaram, S.
Abstract : Sufficient conditions for uniform stability and uniform asymptotic stability of impulsive integrodifferential equations are investigated by constructing a suitable piecewise continuous Lyapunov-like functionals without the decresent property. A result which establishes no pulse phenomena in the given system is also discussed.